The Awareness Level on Financing Long Term Care Cost Among Rural-Urban and Marital Status in Malaysia - Md Yusuf, Mazlynda; Safwan Hamdy, Muhammad; Athirah Ruslan, Nur; Yazis Ali Basah, Mohamad (International Journal of Engineering and Technology, 2018)
The increase in the number of older populations has raised concerns globally.Â This demographic changes is due to the increase in life expectancy and declines in fertility as well as mortality rates.Â Malaysia is also currently experiencing the demographic changes and these changes leads to concerns on the uncertaintiness of future family care and the need for long-term care services.Â Therefore, this study investigates on the level of awareness on financing long term care cost between rural and urban residential area and marital status amomg respondents in Malaysia. 452 responds were analysed using multiple linear regiression model to identify the variables that influenced the level of acceptance and awareness towards long-term care cost.Â Findings show that dependency towards retirement income is significant from urban-rural residents and among single respondents. Health status is also significant for both rural-urban and marital status. However, literacy towards the long term care cost is significant among respondents residing in urban areas only and also married couples. The findings are beneficial and relevant to demonstrate on the importance of financial planning to fund for future long-term care costs.Â